Modeling and implementation of space vector modulation for three-phase direct torque control matrix converter - Ruzlaini, Ghoni (2013)
Matrix converter (MC) as induction motor drivers have received considerable attention because of its high integration capability and the higher reliability direct AC-AC power converter without any bulky DC link component. It can provide sinusoidal output current and input current, adjustable input power factor, and regeneration capability; and very attractive in areas where volume, efficiency and reliability are important. Widespread, systematic, and in-depth studies have been focused on the modulation algorithm and the commutation strategy of the MC, and the key technologies for its application in induction motor drive system. In this thesis, the main aim is to improve the performance of the induction motor drive based on the space vector modulation (SVM) method. In addition, some improvement is performed which are by using close-loop induction motor drive controller based on the relations of the efficiency and power factor with the rotor frequency and slip frequency in a steady state mathematical model and second, enhancing this controller by replacing the PI controller with the combination of Direct Torque Control (DTC) and Particle Swarm Optimization (PSO). The combination of DTC-PSO technique generates the required voltage vectors under 0.86 input power factor operations and it also gains the change regularity between efficiency and power factor. The duty cycles of the switches are modeled using SVM for 0.65 voltage transfer ratios. The mathematical models for the proposed systems are implemented by using Matlab/Simulink for different speed and load. Finally, the whole system has been verified from the experiments and the output voltage, and the input current generated by the model of the converter. The results demonstrate the good quality and robustness in the system dynamic response and a reduction in the steady-state and transient motor ripple torque.